Research on the technological process of restoration with electrodiffusion strengthening of the working surfaces of the segments of the headers of combine harvesters - Marchenko, D.D.; Matvyeyeva, K.S. (Problems of Tribology, 2025)
The paper presents a study of the technological process of restoring the working surfaces of combine harvester header segments using electrodiffusion strengthening (EDS). The EDS of restored Duracut Knife Sections was experimentally investigated. With a current density the ratio between the hardness of the front and rear surfaces of the blade was observed . The relative wear resistance of the restored segments with EDS hardening was on average 1.3 times higher than that of new segments. Quantitative microanalysis of the chemical composition across the cross-section of the EDS-treated segments revealed an increase in the concentration of alloy-forming components in the hardened surface by 1.2 times. As a result of diffusion segregation, the concentration of elements increased. Larger values were observed on the rear surface of the restored segment’s blade. A technological process for restoring the working surfaces of the Duracut Knife Sections of the John Deere combine harvester header using EDS has been developed. The proposed technology allows for the restoration and strengthening of the working surfaces of segments in grain harvesting and forage harvesting combines, as well as mowers. For the EDS-hardened segments, the blade thickness were maintained after the operational tests, indicating the presence of the self-sharpening effect.